Implications of increasing pollution levels on commercially important fishes in Lake Victoria - Badamasi, Inuwa; Odong, Robinson; Masembe, Charles (Journal of Great Lakes Research, 2019)
Lake Victoria receives huge quantities of effluent from domestic, agricultural and industrial sources. We used fish condition factor (K), vitellogenin (VTG) production and liver lesions as biomarkers to assess pollution levels in the lake. We tested the hypothesis that pollution levels do not affect the selected biomarkers. Beach seine and cast nets were used to collect Oreochromis niloticus (n = 230), Lates niloticus (n = 99) and Protopterus aethiopicus (n = 37) in areas presumed to be less or more polluted, both inshore and offshore. K was lower in more polluted compared to less polluted areas of the lake. VTG production was high in both less and more polluted areas for O. niloticus (0.77 ± 0.08 mg/L), L. niloticus (0.73 ± 0.09 mg/L) and P. aethiopicus (0.55 ± 0.06 mg/L). Liver tissue showed lesions such as vacuolations, cellular degeneration, sinusoidal dilation, focal necrosis, increased Küpffer cells and congestion of sinusoids. The prevalence of liver tissue alteration showed normal lesion (19.9%, n = 73), slight (8.2%, n = 30), moderate (41.5%, n = 152), severe (18.6%, n = 68) alterations and irreparable damage (11.8%, n = 43). Severe liver alterations in O. niloticus, L. niloticus and P. aethiopicus were higher in more polluted compared to less polluted areas. Chemical contamination of Lake Victoria caused liver lesions and other changes in fishes, possibly leading to adverse effects on the lake’s fisheries resources. Overtime, such chemical contamination could lead to negative impacts on the consumers of fish if actions are not taken to mitigate the risks.
Keywords: Environmental pollution; Lake Victoria; Lates niloticus